ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN SAHAM PERDANA DI BURSA EFEK INDONESIA - Martha Rianty (JURNAL KOMPETITIF, 2019)
ABSTRACT This research aimed to know existence the influence of Profitability (ROA), financial leverage, reputation of underwriter, reputation, firm SIZE, and AGE company  which IPO in Indonesia Stock Exchange in the year 2010-2012. Population used is the companies that go public on the Indonesia Stock Exchange by taking a sample of firms in 2010-2012, while the sample is an experienced company IPO underpricing as many as 34 companies, with a sampling purposive sampling technique. Type of data used are secondary data. Data collection method used is the documentation.Analysis tool used is multiple linear regression using the t test and F test. The results of this study is the percentage of share effect significant positive the company's stock underpricing. Condition of market, financial leverage, and profitability had no significant effect the company's stock underpricing. Keywords: Underpricing, Initial Public Offering (IPO), Reputation of Underwriter,Reputation Auditor, Age Company, Firm Size , Profitability Company ( ROA) and of Financial Leverage